Production of Eugenol by Endophytic Fungi Isolated from Cloves (Syzygium aromaticum) from Marikurubu and Tongole - Arini Zahrotun; Tamalia Tama; Utami Sri Hastuti; Fatchur Rohman; Endang Suarsini (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Endophytic fungi are known to produce secondary metabolites with potential applications in the field of health, including flavonoids, terpenoids, tannins, and eugenol. The use of eugenol from clove (Syzygium aromaticum) plants has been widely studied to optimize its benefits. This study aims to evaluate the production of eugenol by endophytic fungi isolated from clove organs collected from Tongole and Marikurubu. The isolated endophytic fungi were identified as follows: Rhizoctonia sp., Diplococcium sp., Geotrichum candidum, Eupenicillium javanicum, Penicillium frequentans, and Aspergillus nidulans. Eugenol content was analyzed using gas chromatography (GC). The results showed that eugenol production varied significantly among isolates, with Geotrichum candidum from Marikurubu (0.44111 μg/mL) and Aspergillus nidulans from Tongole (0.37972 μg/mL) exhibiting the highest concentrations. In contrast, other isolates showed relatively low production levels. These findings suggest that eugenol biosynthesis is strongly influenced by fungal species rather than organ origin or sampling location. This study highlights the potential of selected endophytic fungi as an alternative source of eugenol.